2012
DOI: 10.1074/jbc.m111.294470
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Accumulation of the Activated Epidermal Growth Factor Receptor (EGFR) Induces Apoptosis

Abstract: Background: EGF receptor (EGFR) signaling is regulated by endocytosis. Results: The intracellular localization of the EGFR affects its signaling. Conclusion: EGFRs on the limiting membrane of endosomes, but not from the intraluminal vesicles, can induce apoptosis. Significance: EGFR signaling is spatially regulated at multiple steps of the endocytic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 27 publications
11
91
1
Order By: Relevance
“…The authors have used monensin to block endosomal trafficking of EGFR. As EGFR accumulation and activation pattern shown in the current study largely exceeds the magnitude of EGFR accumulation shown previously (37), it is reasonable to propose that cell death is probably the terminal outcome of myoferlin depletion. The present results confirm this and show a strong induction of apoptosis in myoferlin deficient, EGF-stimulated cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors have used monensin to block endosomal trafficking of EGFR. As EGFR accumulation and activation pattern shown in the current study largely exceeds the magnitude of EGFR accumulation shown previously (37), it is reasonable to propose that cell death is probably the terminal outcome of myoferlin depletion. The present results confirm this and show a strong induction of apoptosis in myoferlin deficient, EGF-stimulated cells.…”
Section: Discussionsupporting
confidence: 55%
“…Same is the case with Raf kinase (36), where high-intensity Raf signal causes cell-cycle arrest; this is in contrast to the normally assumed proproliferation function. Recently, Rush and colleagues (37) have shown that high endosomal accumulation of activated EGFR induces apoptosis in MDA-MB468 cells. The authors have used monensin to block endosomal trafficking of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular tyrosine kinase receptor signaling has also been established through studies of EGF receptor (EGFR) endosomal accumulation. One study (63) has identified cell surface EGFRs as promoting cell growth and intracellular EGFRs as inducing apoptosis. Another study (66) has identified the presence of ERK-MAPK components on EGFR-containing endosomes and the presence of ligand-bound EGFRs on endosomes, suggesting the occurrence of EGFR endosomal signaling.…”
Section: Cd31mentioning
confidence: 99%
“…HeLa cells express physiological levels of EGFR and are a wellcharacterized model for the study of EGFR trafficking (Ley and Ellem, 1992;Rush et al, 2012). Stimulation of HeLa cells using a range of EGF concentrations caused EGFR activation, as assessed by an increase in phosphorylated ERK1 and ERK2, and high concentration EGF elicited a marked downregulation of EGFR (supplementary material Fig.…”
Section: Ligand Concentration and Rin1 Function Determine Egfr Ubiquimentioning
confidence: 99%